Mechanical and tribological behaviour of PA6 and short aramid fiber composites - George Catalin CRISTEA (National Institute for Aerospace Research “Elie Carafoli” - INCAS, 2021)
This paper presents the results of mechanical and tribological characteristics for two composites: PA6 as matrix and 5% aramid whiskers as additive material and PA6 + 10% aramid whiskers, comparing them to those made of PA6 (polyamide 6). To improve the mechanical and thermal properties of polyamide (PA6), the composites were prepared via the Brabender lab mixer and mould forming under given pressure and temperature conditions. Test specimens made of pure PA6 and PA6 mixed with 5 wt.% and 10 wt.% aramid whiskers were subjected to mechanical tests (three-point bending and impact), thermo–mechanical test (HDT - heat deflection temperature), tribological test (block-on-ring) and analyzed from morpho-structural point of view. Compared to the PA6 samples, the mass concentrations of aramid whiskers improved the HDT deflection temperature values. In the case of samples with 5% aramid whiskers, the absorbed energy increased by 13% and for those with 10% aramid whiskers they increased by 30%. Aramid whiskers-doped materials performed much better on severe tribological testing as compared to PA6 samples. Increasing the deflection temperature, also improved their resistance from a tribological point of view.